2018
DOI: 10.1021/acs.jpcc.7b09184
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Down-Shifting and Down-Conversion into Metal–Organic Frameworks to Enhance the Spectral Conversion for Solar Cells

Abstract: Luminescent spectral conversion, including down-conversion (DC) and down-shifting (DS) is a potential route to overcome the spectral mismatch between solar photons and the semiconductor energy gap. Here, we introduce metal organic frameworks (MOFs) that integrate DC and DS processes into one system. Three different MOFs (Gd­(BTC)­(1), Gd­(BPT)­(2), and Gd­(OBT)­(3)) were synthesized doped with lanthanide ions couples. The DS–DC synergistic fluorescent processes were observed in all the MOFs. The overall absorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…18 Compared to conventional inorganic phosphors, luminescent lanthanide coordination polymers provide unique opportunities for developing new emission materials due to their simple synthesis, controllable structure, abundant spectra as well as excellent thermostability. 19 However, pure lanthanide complexes have not been applied extensively in practical applications due to their photothermal instabilities, poor mechanical properties, and sensitive quenching effect to concentration or solvent molecules. 20 Therefore, to incorporate lanthanide emission species into polymer matrices could be a prerequisite for developing their practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…18 Compared to conventional inorganic phosphors, luminescent lanthanide coordination polymers provide unique opportunities for developing new emission materials due to their simple synthesis, controllable structure, abundant spectra as well as excellent thermostability. 19 However, pure lanthanide complexes have not been applied extensively in practical applications due to their photothermal instabilities, poor mechanical properties, and sensitive quenching effect to concentration or solvent molecules. 20 Therefore, to incorporate lanthanide emission species into polymer matrices could be a prerequisite for developing their practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, other rare-earth containing materials are also being used for increasing the solar cell efficiency like metalorganic framework with RE 3+ ions, dye-sensitized solar cells with rare-earth materials, and perovskite materials doped with luminescent RE ions (Goldschmidt and Fischer, 2015;de la Mora et al, 2017;Zhou et al, 2017;Yu et al, 2018).…”
Section: Enhancing the Photovoltaic/solar Cell Efficiencymentioning
confidence: 99%
“…Here, Yu et al utilized Tb 3+ or Dy 3+ as bridging ions to modulate the Δ E and enhance the efficiency of EnT in Yb 3+ ‐doped MOFs. [ 68 ] The EnT efficiency in MOFs containing bridging ions is about threefold higher than in MOFs that have no bridging ions. The researchers in Yu's group also demonstrated that bridging ions such as Dy 3+ significantly increase the QY of Yb 3+ emission from 1.58% to 5.30%, which is close to the highest possible value of 5.88% for Yb 3+ coordination compounds containing CH bonds.…”
Section: Engineering Ent Processes In Mofsmentioning
confidence: 99%